UPAYA-UPAYA PEMULIHAN DIRI MANTAN LESBIAN - Nurul Fatimah, Puti (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
AbstractThe goal of this research is to find out the cause of ex lesbian make seriouseffort to back in normal live and what kinds of effort that can be done by thelesbian to be a normal. This research used qualitative method. The researchdata are executed by observation and interview with two subjects with rangeof age between 17 years old until 21 years old and both of them are totallyheal. The first conclusion of this research is the cause of the both subjects wantto be recovered is being a lesbian is not guarantee that they can achieve thetrue happines, beside that being a lesbian, they will not give an offspring. Bothof subjects will not endure with pressure and felt guilty, and will not survive withlesbian live. Guilty mind towards the family, peoples that they love even feltguilty with God. Second conclusion that the effort that be done by ex lesbian ismade a commitment to change, self regulation, recognizing environment whichable to help recovery effort, able to self control, and create the maintenanceprogram.Keywords: Ex Lesbian